TWO YEARS EFFECTIVENESS OF RITUXIMAB IN REFRACTORY IDIOPATHIC THROM-BOCYTOPENIC PURPURA - Majdi H. Al-Jadayeh; Mohammad B. Obeidat; Mohammad B. Obeidat; Ayman S. Abou-Kamar; Anees I. Alhalalmeh; Ahmad A. Shahin; Qutaiba S. Nuseir; Abdulmajeed M. Arabiat (National Journal of Medical Research, 2019)
Background and aim: The treatment of immune thrombocytopenia (ITP) started with steroids but most patients will relapse or have significant adverse effects. The use of Rituximab was greeted enthusiastically: it led to up to 60% response rates, making it the main alternative to splenectomy, with far fewer side effects. The aim of study to assess the 2 years effectiveness of rituximab in the managements of patients with chronic and refractory immune thrombocytopenic purpura (ITP).